The use of marine wildlife-watching codes and their role in managing activities within marine protected areas in Scotland. (November 2016) - Inman, Anna; Brooker, Esther; Dolman, Sarah; McCann, Rona; Wilson, A. Meriwether W.
Abstract: Marine wildlife-watching is a developing industry in Scotland contributing to overall growth and aspirations of the marine tourism sector. Despite European-level legal protection of cetaceans, and Scottish legislation for the protection of seals at designated haul-out sites, there are currently no formal or mandatory regulations to specifically manage tourism activities in relation to marine wildlife. However, most Scottish wildlife-watching operators adopt one, or more, of the five key voluntary codes of conduct which have been developed in the UK since 2003. In this paper, we review the consistency of policy messages and recommendations across voluntary codes of conduct for the UK and Scotland, taking into consideration global use and effectiveness in the use of similar codes. In this context, we specifically examine the potential impacts of wildlife watching and management of future activities, both within and outwith marine protected areas (MPAs) in Scotland. For this, the research also incorporates data from field surveys, in-situ observations and operator questionnaires conducted in Scotland relating to the implementation of the codes in practice. Key findings highlighting inconsistences in some of the key recommendations across the five UK codes in particular, the distance and speed when approaching an animal. However, all of the codes also have some similarities, including advising against deliberate human interaction, e.g. swimming with marine megafauna, including a separate code on basking sharks, published by the Shark Trust in the UK. In light of the growing network of wildlife-focused MPAs in Scotland (in particular the Sea of Hebrides proposed MPA for mobile species), and national aspirations for the growth of the marine tourism sector, we consider the potential implications of unregulated wildlife watching and the conservation objectives of protected areas for marine mammals and basking sharks. We also provide recommendations on how more formal wildlife-watching regulations could enhance MPA effectiveness and contribute to the emerging processes for Regional Marine Plans across Scotland and provide some insights for global marine wildlife tourism. Highlights: The five main Scottish codes are inconsistent in key messages and policies. All Scottish codes advise against deliberate human interactions (such as swim-with). A single, comprehensive code would be more suitable and measureable. Further research is needed on environmental impacts of marine wildlife watching.